2018
DOI: 10.1016/j.immuni.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Extrathymically Generated Regulatory T Cells Establish a Niche for Intestinal Border-Dwelling Bacteria and Affect Physiologic Metabolite Balance

Abstract: The mammalian gut microbiota provides essential metabolites to the host and promotes the differentiation and accumulation of extrathymically generated regulatory T (pTreg) cells. To explore the impact of these cells on intestinal microbial communities, we assessed the composition of the microbiota in pTreg cell-deficient and -sufficient mice. pTreg cell deficiency led to heightened type 2 immune responses triggered by microbial exposure, which disrupted the niche of border-dwelling bacteria early during coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 65 publications
11
93
0
Order By: Relevance
“…These RORγt+ Tregs are induced by the presence of complex microbiota and provide anti-inflammatory functions [50] and have been shown to have a distinct repertoire [51]. For example, RORγt + pTregs responsive to the short-chain fatty acid (SCFA) butyrate are generated in the gut [42] where they function to establish border-dwelling bacteria that protect against microbial exposure and normal metabolite profiles [43]. Therefore, we hypothesized that there would be a reduction in the Helios − and RORγt + pTreg populations in NOD CNS1 −/− females.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These RORγt+ Tregs are induced by the presence of complex microbiota and provide anti-inflammatory functions [50] and have been shown to have a distinct repertoire [51]. For example, RORγt + pTregs responsive to the short-chain fatty acid (SCFA) butyrate are generated in the gut [42] where they function to establish border-dwelling bacteria that protect against microbial exposure and normal metabolite profiles [43]. Therefore, we hypothesized that there would be a reduction in the Helios − and RORγt + pTreg populations in NOD CNS1 −/− females.…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiome might be linked to T1D due to the fact that the pLN is also a draining site for microbial antigens [59], and autoreactive cells have also shown cross-reactivity between microbial antigens and islet antigens [60,61]. In fact, recent characterization of the B6 CNS1 −/− mouse directly revealed that defects in gut pTreg generation alter gut microbiome colonization [42,43]. Since there is a change in gut Tregs in both NOD CNS1 −/− models generated, the ability to observe a similar disease phenotype in our NOD CNS1 −/− model might be masked by differences in gut microbiome composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal Tregs therefore appear well suited to avoid unwanted immune reactions to such ubiquitous antigens (1,2,4). As can be expected, the majority of Tregs in the mouse colon are microbial-specific (5)(6)(7), whereas most Tregs in the mouse SI respond to food antigens (4).…”
Section: Introductionmentioning
confidence: 85%
“…For example, colonization by a subset of Clostridia enhanced anti-inflammatory phenotypes in mice 3 , and enrichment in specific members of the Bacteroides and Parabacteroides genera induced CD8+ T cell responses and anticancer activity in mice and marmosets 4 , as well as correlating with the abundance of these immune effectors in humans 5 . A multitude of experiments in mice have allowed for the determination of mechanisms by which intestinal mucosal-associated bacteria affect host physiology at the epithelial interface and systemically throughout their host 6,7 .…”
Section: Introductionmentioning
confidence: 99%